95 Lack of Evidence for Reduced Efficacy of Medical Therapy for Heart Failure in Older Adults. (16th March 2021) - Cox-Smith, A; Cooper, T; Punjabi, P; Barton, C; Levy, S; Plymen, C; Cole, G
Abstract: Introduction: There are almost a million people with heart failure (HF) in the UK; the incidence increases sharply with age. Older adults receive less evidence-based therapy with few trials specifically examining therapeutic efficacy in older age groups representative of a contemporary UK HF population. Concern that efficacy is less in older adults may underlie under-prescription. With important recent advances in HF therapy, we reviewed the contemporary evidence base for any signal of different efficacy in older adults. Methods: We reviewed recent RCTs of medical therapy for heart failure alongside meta-analyses updated with recent therapies including Angiotensin-Neprilysin inhibitors and SGLT2 inhibitors. For those trials in which effect size was presented for age subgroups we compared the effect size. Results: Of 68 randomised controlled trials, 10 presented effect sizes for different age groups. The median average cut-off between younger and older age groups was 66 years (IQR 65 to 72.5 years) and the highest cut-off used was 75 years. The median hazard ratio was 0.77 (IQR 0.67 to 0.80) for the younger age group and 0.76 (IQR 0.73 to 0.88) for the older age group. In 8 of the 10 trials, the effect size in the oldest age group was statistically significant on its own including Sacubitril-Valsartan and Dapagliflozin. Conclusion: When considering the medical therapeutic armamentarium for heart failure as a totality, there is no evidence it is any less effective in older adults than younger adults. The recent Zannad et al cross-trial analysis supported this showing significant additional life years in the patients over 80 years on HF therapy. Whilst there may be practical and frailty-related reasons for not prescribing life-prolonging therapy, the proportional survival benefits of these medications is similar in older adults. This should be utilised where practically possible and discussed with patients when making an informed choice.